Application of the Internet of Things (IoT) based digital platform for â€œPeduli, Keamanan, dan Ketertibanâ€ (PEKERTI) - Fadlika, Irham; Afandi, Arif Nur; Gumilar, Langlang; Andriansyah, Muhammad Rizal; Mistakim, Eka; Fakhri, Achmad Syahrudin; Gunawan, M. Ricko (University of Merdeka Malang, 2022)
This community service program is implemented in RT 09 RW 06 Penanggungan Village, Klojen District, Malang City. This is a housing estate that is located close to several campuses, making it vulnerable to being a crime target. In this program, we present an idea to solve this problem by creating an Internet of Things (IoT) based Android application â€œPeduli, Keamanan, Ketertiban